Intonation als eine wichtige komponente der kommunikationsfähigkeit [Articol] - Pomelnicova, Ana (USARB, 2019)
A lot is spoken about forming the phonetic competence in foreign language schools. Thus, this article deals with the importance of the sound (phonetic) aspect of oral communication in foreign language teaching where special attention is paid to intonation. There is a central object of study from the perspective of spoken speech parameters. Future professionals must speak a foreign language, have interpersonal and professional communication skills. These skills allow you to feel confident in a foreign business environment, to be competitive in the labour market. But it is worth mentioning that the knowledge of vocabulary and grammatical rules is insufficient for this. It is necessary to identify the main point, accents and pauses. The author states that intonation, emotions, skills intoning sentences are very important in a foreign language. Thus, the given article discusses the functions of intonation, emphasizing the main features of the intonation of the German language and indicating their syntactic and phonetic peculiarities.
Keywords: foreign language skills; language learner; the phonetic aspect; intonation; oral communication; systemic intonation analysis